1996
DOI: 10.1016/s0022-5223(96)70220-9
|View full text |Cite
|
Sign up to set email alerts
|

Cost reduction by combined carotid endarterectomy and coronary artery bypass grafting

Abstract: A significant cost reduction is likely if patients who require coronary artery bypass grafting with significant carotid stenosis have simultaneous carotid endarterectomy and bypass grafting, provided risk is not increased. To investigate this issue, we retrospectively identified cases from February 1977 to May 1994 with first-time isolated carotid endarterectomy, coronary bypass, or combined procedures. In the isolated carotid endarterectomy population, median age was 69 years and 58% (85/146) were male, as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 46 publications
3
25
0
2
Order By: Relevance
“…[6][7][8] Combined one-stage CABG and CEA has advantages over the two-stage procedures, including shorter hospital stays, decreased exposure to anesthesia, and decreased costs. 9) Although an earlier study by Hertzer and colleagues 4) reported elevated stroke and mortality rates after the combined approach, many other large series have not reported the higher strokes and mortality rates found in earlier studies. 10,11) On the other hand, there is an increased risk of myocardial infarction and death with no difference in stroke rates among patients undergoing staged procedures as reported by the European Carotid Surgery Trial and Brener and colleagues.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[6][7][8] Combined one-stage CABG and CEA has advantages over the two-stage procedures, including shorter hospital stays, decreased exposure to anesthesia, and decreased costs. 9) Although an earlier study by Hertzer and colleagues 4) reported elevated stroke and mortality rates after the combined approach, many other large series have not reported the higher strokes and mortality rates found in earlier studies. 10,11) On the other hand, there is an increased risk of myocardial infarction and death with no difference in stroke rates among patients undergoing staged procedures as reported by the European Carotid Surgery Trial and Brener and colleagues.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, they reported the combined one-stage CABG and CEA has advantages over the twostage procedure, including a shorter hospital stay, decreased exposure to anesthesia, and decreased costs. 9) We believe that the rational approach for all patients who present with severe combined arterial disease is to perform one-stage combined CAE and CABG. In this context, one-stage operations can be done either simultaneously or staged procedures conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Mean hospitalization following combined surgery may range from 10.3 to sixteen days, 26,36 and mean ICU stay, from 3.6 to four days 13,18 . Respiratory complications occurred in up to 12% of the patients 14 , acute renal failure in 6% 14,36 , bleeding requiring surgical reintervention in 5% 36 ; wound infection and hematoma in 4% 10,36 ; low cardiac output syndrome (LCOS) from 0.6% to 4% 8,36 , arrhythmias in up to 33%, and atrial fi brillation from 0 to 34% 15 .…”
Section: Resultsmentioning
confidence: 99%
“…In some series, CABG was preceded by CE under the same anesthesia without extracorporeal circulation (ECC) 7,9,12,17,26,36 . Still, Khaitan et al 13 have reported good results with the combined procedure using ECC.…”
Section: Surgical Indication and Techniquementioning
confidence: 99%
See 1 more Smart Citation